2019
DOI: 10.3389/fgene.2019.00718
|View full text |Cite
|
Sign up to set email alerts
|

Novel Neonatal Variants of the Carbamoyl Phosphate Synthetase 1 Deficiency: Two Case Reports and Review of Literature

Abstract: Carbamoyl phosphate synthetase I (CPS1) deficiency (CPS1D), is a rare autosomal recessive disorder, characterized by life-threatening hyperammonemia. In this study, we presented the detailed clinical features and genetic analysis of two patients with neonatal-onset CPS1D carrying two compound heterozygous variants of c.1631C > T (p.T544M)/c.1981G > T (p.G661C), and c.2896G > T (p.E966X)/c622-3C > G in CPS1 gene, individually. Out of them, three variants are novel, unreported including a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Successful gene therapies have been described for the other enzymes in the urea cycle [137][138][139][140] , and these new studies in CPS1 deficiency lay the groundwork for rescuing the more severe neonatal phenotype in the constitutive knock out and potential clinical translation. With over 250 unique mutations reported, and >90% of them being private mutations 141 (arising in single families only), a successful gene addition approach has the potential to benefit all CPS1 deficiency patients.…”
Section: Emerging Therapeuticsmentioning
confidence: 99%
“…Successful gene therapies have been described for the other enzymes in the urea cycle [137][138][139][140] , and these new studies in CPS1 deficiency lay the groundwork for rescuing the more severe neonatal phenotype in the constitutive knock out and potential clinical translation. With over 250 unique mutations reported, and >90% of them being private mutations 141 (arising in single families only), a successful gene addition approach has the potential to benefit all CPS1 deficiency patients.…”
Section: Emerging Therapeuticsmentioning
confidence: 99%
“…To date,hundreds of CPS1D cases have been reported worldwide (Häberle et al, 2011). To our knowledge, the frequency of CPS1D has not been investigated in Chinese cohorts and only eight Chinese patients with CPS1D, including the patient in the present study, have been reported (Chen et al, 2013(Chen et al, , 2018Yang et al, 2017;Zhang et al, 2018;Yan et al, 2019). Table 1 summarizes the results of the present study together with those for seven previously reported Chinese patients.…”
Section: Discussionmentioning
confidence: 52%
“…According to previous studies, a few cases of CPS1 deficiency with only a single-allele mutation have been reported (Table 2) (13)(14)(15)(16)(17). Further studies are needed to determine whether or not this patient has mutations in the other alleles that could not be detected through conventional genetic analyses or whether the slightly low CPS1 activity in this patient was further reduced by some acquired factors.…”
Section: Discussionmentioning
confidence: 86%